Clinical implications of clopidogrel resistance - De Miguel, Antonio; Ibanez, Borja; Badimón, Juan José (Thrombosis and Haemostasis, 2008)
The benefits of clopidogrel in the treatment and prevention of coronary artery disease are well established, however, not all individuals respond in the same way to clopidogrel; there are patients who suffer adverse events despite clopidogrel treatment. This review focuses on the definition, potential mechanisms for and clinical implications of clopidogrel resistance, as well as the strategies to improve the response to this antiplatelet drug. There is an inter-individual variability in response to clopidogrel therapy, and a sub-optimal response (clopidogrel resistance) has been associated with adverse cardiovascular events. Nevertheless, there is no clear and consensual definition of clopidogrel resistance. Response to clopidogrel therapy follows a normal, bell-shaped distribution, so a more appropriate description would be variable response rather than clopidogrel resistance. Independent of the term used, lower response to clopidogrel therapy seems to be associated with a higher probability of suffering thrombotic events. Due to the misleading definition of resistance and non-standardized method for assessing platelet inhibition, current guidelines do not recommend the use of platelet function assays to monitor the inhibitory effect of antiplatelet drugs. Current guidelines also do not recommend clopidogrel loading doses higher than 300 mg and daily maintenance doses higher than 75 mg, even though a regimen of 600 mg clopidogrel loading dose seems to be preferred for patients undergoing percutaneous coronary interventions.
Keywords: Clopidogrel resistance; variable response; platelet function assay; percutaneous coronary intervention; late in-stent thrombosis